Experimental investigation of diesel soot oxidation reactivity along the exhaust after-treatment system components. (15th October 2021) - Liang, Xingyu; Lv, Xu; Wang, Yajun; He, Lijun; Wang, Yuesen; Fu, Kaixuan; Liu, Qingling; Wang, Kun
Highlights: Soot exhibited higher graphitization degrees along the after-treatment system components. Aliphatic C–H groups in soot more likely to oxidize than other surface functional groups. Soot particles further transformed in the exhaust after-treatment system. Activation energies of soot oxidation determined 132–190 kJ/mol by the Arrhenius model. Abstract: The primary objective of the present study is to investigate the variations of soot particles' oxidation reactivity along the components of the exhaust after-treatment system in a diesel engine and analyze its quantitative correlation with surface functional groups (SFGs) and graphitization degree. Soot particles generated from a 16-cylinder turbocharged diesel engine were sampled thoroughly before and after the diesel oxidation catalyst (DOC), as well as after a catalyzed diesel particulate filter (CDPF). Using a set of characterization techniques of Fourier transform infrared (FTIR), Raman spectroscopy and Thermal gravimetric analyzer (TGA), the surface functional groups (SFGs), graphitization degree and oxidation reactivity of soot particle samples along the exhaust after-treatment system components were examined. Results showed that, for all conditions, soot oxidation activation energies increased almost linearly along the after-treatment system, indicating that soot particles became more and more stable, with the inherent graphitization degree achieved the highest right after the CDPF. Meanwhile, the combined characterization results also indicated that amorphous carbon and reactive light volatile fractions have been removed or oxidized via passing through the DOC and CDPF monolith. It was thus concluded that the higher oxidation activity of soot particles was characterized by lower graphitization degree and higher aliphatic C-H group concentration. The catalyst components in the after-treatment systems (DOC and CDPF) effectively increases the graphitization of the exhaust particles, leaving more stable particles that would require much higher energies from active regeneration or more powerful catalysts on the CDPF wall surface to clean them up.